David Frank Adjaye Design Thinking: Pendekatan the Unfold Cinematically - Hadi Jaya Putra; Prisca Bicawasti Budi Sutanty; Sarah Nadia (ATRIUM: Jurnal Arsitektur, 2022)
Title: David Frank Adjaye’s Design Thinking: The Unfold Cinematically Approach   Design thinking is fundamental to every designer because it becomes a strategy that creatively solves design problems. Adjaye, an architect with various degrees and awards, explicitly stated that the approach used was "The Unfold Cinematically". The excellence of this approach deserves to be expressed to provide insight and inspiration, that designing is not by generalizing the form of design, because every place has its uniqueness. The method used is descriptive qualitative. Data was collected from literature studies, books, articles, and official websites that refer to Adjaye and his works. The results of this study show that this approach reflects his life journey from moving countries so that the character to respect differences in cultural values is formed. "The Unfold Cinematically" then developed into a link between the process consisting of "The Inside" and "The Outside". The conclusion is that the formation of design thinking is a process of a long life journey. Sensitivity to various conditions determines the formation of an architect’s design thinking. The approach of "The Unfold Cinematically" summarizes Adjaye’s focus on the livelihood of social activities and physical forms that are formed from the environment of values held by the community.